Mundus librorum w Nieświeżu. Magnacka tożsamość a duchowość zakonna - Pietrzkiewicz, Iwona (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
Nesvizh (Nieśwież) - the town of the Radziwiłł family, and at the same time the centre of the activity of a number of monastic institutions, especially the Jesuits sponsored by Mikołaj Krzysztof Radziwiłł - is an interesting example of how magnate religiosity was built and what was its scope. The renunciation of Calvinism and the model of miles christianus implemented over the years became the basis for Radziwiłł’s religious, social, and political activities, but it was also continued by his successors, the successive guardians of the Nesvizh estate. Their role model that combined models of a citizen, a Christian and a believing Church’s religious attitude was built on personal contacts, reading, and texts produced in the surroundings of the court or at his request. This model being perpetuated in communication, texts created for and inspired by ordinands and their families is the best example of coexistence and mutual influence of secular and the ecclesiastical communities in creating and strengthening the identity of the magnates in the context of the roles proposed and ennobled by orders in the post-Tridentine era.